Controle de ativos, principais problemas nos sistemas ERPs e falhas nos controles internos - Costa, Alcidis Ferreira da (2023)
With the evolution of accounting, administrative science has adopted asset management as one of the practices of internal controls. In this sense, the objective of this research was to identify the problems in the controls of fixed and intangible assets, and in the end the expected contribution is to present a software artifact or Shadow System that together with the ERP or individually can remedy or minimize the failures in the management of fixed and intangible assets raised in this study. The methodology used was the qualitative research approach with the application of a questionnaire to a non-statistical sample of accounting professionals in general, which identified a significant demand for an artifact that solves the problems raised in the bibliography. The software artifact developed was tested in 3 different companies over time and presented a satisfactory solution for different needs according to the premises raised in this research. The academic benefits of this study were the contribution to identify the main problems in ERP systems for asset control, as well as the main flaws in the internal controls of these assets, while the benefit to the market was to present a software artifact that in together with the ERP or individually, could solve or minimize such problems